Clinical relevance of miR-mediated HLA-G regulation and the associated immune cell infiltration in renal cell carcinoma - Jasinski-Bergner, Simon; Stoehr, Christine; Bukur, Juergen; Massa, Chiara; Braun, Juliane; Huettelmaier, Stefan; Spath, Verena; Wartenberg, Roland; Legal, Wolfgang; Taubert, Helge; Wach, Sven; Wullich, Bernd; et al. (OncoImmunology, 2015)
In human tumors of distinct origin including renal cell carcinoma (RCC), the non-classical human leukocyte antigen G (HLA-G) is frequently expressed, thereby inhibiting the cytotoxic activity of T and natural killer (NK) cells. Recent studies demonstrated a strong post-transcriptional gene regulation of the HLA-G by miR-152, -148A, -148B and -133A. Standard methods were applied to characterize the expression and function of HLA-G, HLA-G-regulatory microRNAs (miRs) and the immune cell infiltration in 453 RCC lesions using a tissue microarray and five RCC cell lines linking these results to clinical parameters. Direct interactions with HLA-G regulatory miRs and the HLA-G 3' untranslated region (UTR) were detected and the affinities of these different miRs to the HLA-G 3'-UTR compared. qPCR analyses and immunohistochemical staining revealed an inverse expression of miR-148A and -133A with the HLA-G protein in situ and in vitro. Stable miR overexpression caused a downregulation of HLA-G protein enhancing the NK and LAK cell-mediated cytotoxicity in in vitro CD107a activation assays revealing a HLA-G-dependent cytotoxic activity of immune effector cells. A significant higher frequency of CD3(+)/CD8(+) T cell lymphocytes, but no differences in the activation markers CD69, CD25 or in the presence of CD56(+), FoxP3(+) and CD4(+) immune cells were detected in HLA-G(+) compared to HLA-G(-) RCC lesions. This could be associated with higher WHO grade, but not with a disease-specific survival. These data suggest a miR-mediated control of HLA-G expression in RCC, which is associated with a distinct pattern of immune cell infiltration.
EVALuna2:6743